Derivatives Market in India: An Empirical Analysis on Perception of Retail Investors towards Derivatives Market with Reference to Visakhapatnam District: Exploring the Perception of Retail Investors towards Derivatives Market in Visakhapatnam District (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Derivatives market has an important role play in the economic development of a country. The Objective of the study is derivative market problems and prospects. The retail and Intuitional Investors occupied a key role in development of derivatives trading in India. Retail Investors are the major participants in equity derivatives have contributed 54% higher when comparing with Intuitional investment; this study has been taken to identify the retail investor’s perception on derivatives trading. The research design chosen is descriptive. The data was used collected using a questionnaire that consists of close ended questions. Convenient sampling method is employed in Visakhapatnam District. After review the available literature the statically Analysis were performed by using % Analysis, Chi-Square Test and; F-Test.